HUBUNGAN ANTARA PERILAKU IBU RUMAH TANGGA TERHADAP STATUS KARIES GIGI ANAK PRASEKOLAH DI KELURAHAN PEDURUNGAN TENGAH KECAMATAN PEDURUNGAN KOTA SEMARANG - Armitha Hapsari; Sandy Christiono; Rizki Amalina; Rama Putranto (Jurnal Medali, 2013)
Dental caries is a dental hard tissue disease that often occurs especially in preschool children. One of the many factors cause dental caries in preschool children is the role of mother. The importance of housewife role which was emulated by their children particularly dental health can the level of children caries. The aim of this study is to determine the relationship of housewife behavior towards dental caries status of preschool children in the Kelurahan Pedurungan Kecamatan Pedurungan Tengah of Semarang.This research used analytic methods with cross-sectional observational study. The subject of this research was preschool children in kindergarten Tunas Kekancan Mukti and Islamic kindergarten Berlian totaling 82 childrens and 82 mothers. Data collection was obtained through examination of caries teeth of children and housewives behavior was obtained by using questionnaires that its validity has been tested, and then processed. Data analysis includes descriptive analysis and hypothesis test using Pearson Product Moment Correlation test.The result showed that 31,7% houswives belongs to bad behavior score criterion, 43,9% belongs to moderate behavior score criterion and 24,4% belongs to good behavior score criterion. The average housewives behavior is sufficient criteria. Because the data was not normal, the Spearman Rho test was used and found that there is a correlation between housewives behavior towards caries of preschool children. Data analysis of the relationship was not normal so used Spearman Rho test.The result of this research can be conclude that there is a relation between housewives behavior towards caries preschool children in the Kelurahan Pedurungan Kecamatan Pedurungan Tengah of Semarang.Â Keywords : housewife behavior, dental caries preschool childrens, caries status of preschool children